Analysis of Factors Affecting the Decline in The Quality of Building Construction Projects - Rifky, Fariz; Putra, I Nyoman Dita Pahang (CIVED, 2023)
Quality according to planning is one of the most important things in the successful implementation of each construction project. Quality factors when implementing building construction projects are very important to know, especially for construction service providers so that they can find out what factors affect the decline in building construction quality. This study aims to analyse the factors that affect the decline in the quality of building construction. This research was conducted by distributing questionnaires in order to obtain data which will then be analysed and discussed in this study. Respondents of this questionnaire are contractors and consultants. Seven factors are obtained that affect the decline in building construction quality based on the results of questionnaires and data analysis, namely equipment, materials, implementation, environment, cost, human resources, design. Furthermore, the data that has been obtained is tested for validity to ensure that the data obtained is valid and reliable testing is carried out to ensure that the valid data is also reliable. The data was analysed using the relative importance index analysis method with the results of the inaccurate design drawing variable which has the highest RII value of 0.908, then descriptive analysis and obtained the results of the design factor having the highest mean value of 3.511 which means that the design factor has the greatest influence on reducing the quality of building construction.